Evaluation of Social Media Marketing and Operational as the Basis for the Wira Wiri Suroboyo Strategy Using the Race, Fishbone, Ahp, and Swot Methods - Erasmus Reyhan Irvandy; Bambang Syairudin (International Journal Labs, 2026)
Transportation is an essential aspect of daily life, as the entire community relies on it to meet various needs. Rapid population growth and the high mobility of residents in the city of Surabaya have created significant challenges in public transportation management. This study aims to identify the reasons behind the low usage of Wira Wiri Suroboyo and to assess the effectiveness of social media marketing for Wira Wiri Suroboyo. A quantitative approach was employed using a questionnaire as the primary data collection instrument, with purposive sampling applied to select respondents. The study utilizes the Analytic Hierarchy Process (AHP), Reach, Act, Convert, Engage (RACE), Fishbone, and Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis methods. The results of the analysis using the Fishbone diagram show that the root causes of low public interest encompass several factors, including limited public participation, routes that do not cover all densely populated areas, inadequate bus stop facilities, and dependence on the regional budget for operational funding. Based on the SWOT matrix, Wira Wiri Suroboyo is positioned in the maintain quadrant but requires significant improvement in the “Act” aspect of social media engagement. The main strategic priority is to enhance interaction with consumers and provide informative, user-friendly content to build stronger brand awareness. This study concludes that the low usage of Wira Wiri Suroboyo is not solely a transportation issue but also a result of an underdeveloped supporting ecosystem. As a strategic recommendation, the Surabaya Transportation Agency should consistently implement the RACE framework, improve infrastructure (particularly bus stops), and adjust bus schedules at each stop according to actual travel patterns (origin–destination).